The Da'wah Politics of Hassan Hanafi - Hendi Supriatna (International Journal of Islamic Khazanah, 2025)
This research aims to analyze the da'wah politics of Hassan Hanafi, a contemporary thinker who seeks to bridge Islamic tradition with the challenges of modernity. This study examines how Hanafi uses da'wah as a means for social transformation, focusing on his main ideas and their relevance to the Indonesian context. The research methodology uses a content analysis approach to Hassan Hanafi's works, including his books and articles. The data were analyzed critically to identify key themes, arguments, and political implications of his da'wah. In addition, this study also considers the social and political context in which Hanafi developed his thinking. The results of the study indicate that Hanafi's political da'wah emphasizes the liberation of individuals from various forms of conquest, be it political, economic, or intellectual. Hanafi called on Muslims to actively participate in shaping their own society and destiny. He also upholds tolerance for differences of opinion and thought, avoids radical actions, emphasizes a dialogical approach, accommodates modern concepts that contain substantial positive effects, thinks rationally based on divine revelation guidelines, interprets texts written in the Koran and Hadith contextually, and uses independent reasoning. The conclusion is that Hassan Hanafi's political da'wah offers a vision of social transformation that is authentically Islamic and relevant to the contemporary world. His thinking can be a source of inspiration for Muslims in Indonesia and around the world who seek to overcome the challenges of modernity and promote social justice. This da'wah is in line with broader trends in contemporary Islamic thought that seek to address the challenges of modernity and promote social justice.